Harvest Gypsies in the San Francisco News, Oct. 5, 1936 - San Francisco News:::Publisher:::::::::::: (San Francisco News; San Francisco, 2024)
The front page of the San Francisco News Oct. 5, 1936, with the first Harvest Gypsies article including the iconic Migrant Mother photograph by Dorothea Lange.